A Simple Method to Assess Euhydration - Capitán Jiménez, Catalina (2009)
We are still lacking a practical, reliable method to assess acute hydration status. Purpose: To measure the time course of urine volume discarded in response to ingesting a standard volume of water at different levels of dehydration, in an attempt to develop a practical method to assess acute hydration status in humans. Methods: Nine healthy, physically active males, aged 23.5 ± 2.6 years old (mean ± standard deviation) reported to the laboratory after an overnight fast of 10 hours or more. Participants exercised intermittently in an environmental chamber (average temperature and relative humidity = 32 ± 3° C and 65 ± 7%, respectively) until dehydrated to 0, 1, 2 or 3% body mass (BM) on different days; the order of treatments was randomized. Upon reaching the desired dehydration, they ingested a volume of water equivalent to 1.43% of their initial weight in 30 minutes. Urine was collected henceforth every 30 minutes for 5 hours. Results: Discarded urine volumes were larger for 0% BM (1236.8 ± 489.4 mL) than the other conditions (375.3 ± 170.2 mL, 235.9 ± 66.0 mL, and 261.7 ± 51.8 mL for 1, 2, and 3% BM, respectively) (p = 0.001), but there were no statistically significant differences among the latter three (p > 0.05). The cumulative volume differences between 0% BM and the rest of the treatments were already significant at time = 60 min (p < 0.05): average volumes at 60 min were: 8.57, 1.86, 1.04, and 1.31 mL*kg-1 for 0, 1, 2, and 3% BM, respectively. Conclusions: this method allows for a practical verification of an individual'¢â?¬â?¢s acute hydration status, giving him/her a volume equivalent to 1.43%BM and collecting urine for 60 minutes; if the individual discards less than 4.7 mL*kg-1 in that time, he/she is hypohydrated.